Quantum Tunneling Mediated Interfacial Synthesis of a Benzofuran Derivative. Issue 33 (4th July 2019) - Paintner, Tobias; Björk, Jonas; Du, Ping; Klyatskaya, Svetlana; Paszkiewicz, Mateusz; Hellwig, Raphael; Uphoff, Martin; Öner, Murat A.; Cuniberto, Edoardo; Deimel, Peter S.; Zhang, Yi‐Qi; Palma, Carlos‐Andres; et al.
Abstract: Reaction pathways involving quantum tunneling of protons are fundamental to chemistry and biology. They are responsible for essential aspects of interstellar synthesis, the degradation and isomerization of compounds, enzymatic activity, and protein dynamics. On‐surface conditions have been demonstrated to open alternative routes for organic synthesis, often with intricate transformations not accessible in solution. Here, we investigate a hydroalkoxylation reaction of a molecular species adsorbed on a Ag(111) surface by scanning tunneling microscopy complemented by X‐ray electron spectroscopy and density functional theory. The closure of the furan ring proceeds at low temperature (down to 150 K) and without detectable side reactions. We unravel a proton‐tunneling‐mediated pathway theoretically and confirm experimentally its dominant contribution through the kinetic isotope effect with the deuterated derivative. Abstract : Tunnel vision : The hydroalkoxylation of a molecular species adsorbed on a Ag(111) surface has been shown by scanning tunneling microscopy complemented by X‐ray electron spectroscopy and density functional theory to proceed at temperatures as low as 150 K. The proton‐tunneling‐mediated pathway was theoretically disentangled and confirmed experimentally through the kinetic isotope effect.